Falls and Motor Vehicle Accidents as The Most Common Causes of Moderate and Severe Head Injuries in Children Age 3 and Younger - Aycicek Cecen; Merih Is; Erhan Celikoglu (Bagcilar Medical Bulletin, 2017)

(untitled)
Objective: We aimed to evaluate the most common causes of moderate and severe head injury at age 3 and younger.Material and Methods: This is a retrospective study that included 157 children (105 males and 52 females) at 3 years of age or younger who were admitted to our emergency unit for moderate or severe head injury between June 2001 and December 2008. Data on patient age, gender, cause of trauma, clinical signs and symptoms, length of hospitalization, radiological findings, surgery, additional injuries, postoperative and late complications, and mortality were examined.Results: The mean age of the patients was 21.05 months. The most common presentation was deterioration in consciousness. The most common cause of moderate head injury was a fall from 1–2 m at 7–12 months of age, and for severe head injury it was a motor vehicle accident at 19–24 months of age. The most common radiological finding in all groups was a linear fracture. In the moderate head injury group, 16 epidural hematomas (EDH), four subdural hematomas (SDH), two dura-brain lacerations, and two depressed fractures required surgery. In the severe head injury group, 6 SDHs and 5 EDHs required surgery. The major postoperative complications were meningitis, rhinorrhea, epileptic seizures, and subdural fluid collection. The overall mortality rate was 3.18% (5 of 157 patients).Conclusions:In our series of moderate and severe head trauma in patients younger than 3 years, the most common cause of trauma was falling from 1–2 m. For prevention, family caregivers must watch crawlers and toddlers closely.